2020
DOI: 10.1371/journal.pone.0235782
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory Study of EEG Alpha Oscillation and Pupil Dilation in Hearing-Aid Users During Effortful listening to Continuous Speech

Abstract: Individuals with hearing loss allocate cognitive resources to comprehend noisy speech in everyday life scenarios. Such a scenario could be when they are exposed to ongoing speech and need to sustain their attention for a rather long period of time, which requires listening effort. Two well-established physiological methods that have been found to be sensitive to identify changes in listening effort are pupillometry and electroencephalography (EEG). However, these measurements have been used mainly for momentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
63
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 67 publications
13
63
3
Order By: Relevance
“…Our alpha power results are consistent with previous sustained attention effort characterization (Seifi Ala et al, 2020). Where a lower magnitude alpha ERSP was associated with greater listening effort, we found a similar result in our most difficult experimental condition (at-will).…”
Section: Increased Listening Effort Is Associated With Auditory Attention Switchingsupporting
confidence: 91%
See 1 more Smart Citation
“…Our alpha power results are consistent with previous sustained attention effort characterization (Seifi Ala et al, 2020). Where a lower magnitude alpha ERSP was associated with greater listening effort, we found a similar result in our most difficult experimental condition (at-will).…”
Section: Increased Listening Effort Is Associated With Auditory Attention Switchingsupporting
confidence: 91%
“…These states 30 can then be used to control stimuli enhancement which can improve the listener's experience. Altering the relative levels of attended and ignored stimuli can reduce listening effort and enhance attended stimuli entrainment (Seifi Ala et al, 2020;Presacco et al, 2019;Mirkovic et al, 2019). Speech enhancement has the capacity to improve listener quality of life in individuals of all ages and levels of hearing loss (Griffin et al, 2019;Liberman et al, 2016;Ciorba et al, 2012;Griffin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As discussed, the “functional inhibition” hypothesis describes increased alpha power as consequence of inhibition in neural circuits, and decreased alpha power reflects neural engagement by reducing suppression [ 29 , 30 ]. Across studies, there have been observations of both an increase in in alpha power with speech listening difficulty (e.g., [ 27 , 28 , 32 , 56 ]) as well as decreases [ 33 , 57 ]. The difference in directions between these studies may be due to task-based differences or variability in listener strategies to complete the task, in line with the view that alpha power in auditory experiments changes as a function of the goals of the listeners, including selection of task-relevant stimuli [ 31 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though many studies have pointed to more difficult conditions showing an increase in alpha power with more difficult listening conditions (Alhanbali et al, 2019;Dimitrijevic et al, 2019;Petersen et al, 2015;Winneke et al, 2020;Wisniewski et al, 2017;Wöstmann et al, 2015Wöstmann et al, , 2017, there are a number of other studies showing greater suppression of alpha power while listening to speech in a difficult compared to an easy condition. For instance, Hauswald et al (2020) found that parietal alpha power decreased with increased degradation to sentences through vocoding (also, see Hjortkjaer et al, 2020;Hunter, 2020;Seifi Ala et al, 2020). Part of the reason for between study differences may stem from differences in stimulus materials and the task.…”
Section: F I G U R Ementioning
confidence: 99%